There will always be Travellers': certainty as survivance in a new alternative world? - Hope, F (Anthropological Society of Oxford, 2023)
Gypsies, Roma, Travellers and other marginalised groups are often constructed as being present oriented. However, anthropologists working with such groups (Fotta 2019; Howarth 2019) have recently begun to demonstrate ways they do in fact orient themselves towards the future in the face of uncertainty. I will extend this work by examining how New Travellers, who only formed as a mobile group in the UK from the 1970s onwards and have suffered from state violence and high morbidity and mortality rates, attempt to ensure their endurance. Despite their short history and experiences of marginalisation, rather than defining their experience as uncertainty, I argue that New Travellers appear to successfully produce a sense of certainty regarding their shared future. This was captured by one interlocutor asserting that ‘There will always be Travellers', despite the newest in a string of legislation criminalising their lifestyle being rolled out at the time. I thus ask whether and how Gerald Vizenor's (2009) concept of survivance may aid an understanding of this community's future-making activities, such as their modes of child socialisation, the telling of stories and their collective mediation of death. While the notion of survivance is in many ways pertinent, due to its embeddedness in Native American studies I conclude that it may not be wholly appropriate to apply it to the New Traveller context. Instead, extending work on human possibilities (Graeber 2007), I build on Elizabeth Povinelli's (2011) notion of new alternative worlds, proposing that the term ‘alternative worldmaking' may better capture the norms, values and practices through which new groups both produce and preserve their communities.